(untitled) (Acta Polytechnica CTU Proceedings, 2017)
BaTiO3 films deposited onto TiNb and Ti substrates using hydrothermal synthesis method were studied in the presented work. These films are supposed to improve properties of bone implants due to their ferroelectric behaviour, because ferroelectrics induce improved bone formation. A great question is the chemical stability of the used material. It can be crucial for its biocompatibility and possible in vivo application. We studied chemical composition of prepared samples, especially concentration of Ba and Ti and trends of these concentrations stimulated by a solution saline action. The Ba and Ti concentrations were determined by XPS under ultra - high vacuum condition. The BaTiO3 films were investigated as received after the preparation procedure as well as after a long - time treatment in solution saline. Every sample was introduced to the solution saline at first for 1 and later for 3 weeks. Ti concentration almost does not change during our experiments while a meaningful Ba decrease is observed. Nevertheless, barium release seems to slow down with respect to the time of solution saline action. Stability of barium titanate films in a period of several months and an absolute amount of the released barium will be a subject of the next research.